Functional Movement Disorders in Children - Chouksey, Anjali; Pandey, Sanjay (Frontiers in Neurology, 2020)
Functional movement disorders (FMDs) are not uncommon in children. The age at onset may have a bearing in the phenomenological pattern of abnormal movement, risk factors, and response to different treatment modalities in this age group. FMDs in children resemble their adult counterparts in terms of gender preponderance, but risk factors are quite different often influenced by cultural and demographic background. FMDs contribute to a significant proportion of acute paediatric movement disorder patients seen in emergency settings ranging from 4.3% to 23% in different case series. The most common movement phenomenologies noticed in paediatric FMDs patients are tremor, dystonia, gait disturbances, and functional tics. Various social, physical, and familial precipitating factors have been described. Common social risk factors include divorce of parents, sexual abuse, bullying at school, examination pressure, or other education-related issues, death of close friend relative or family member. Physical trauma like minor head injury, immunization, tooth extraction, and tonsillectomy are also known to precipitate FMDs. The response to treatment appears to be relatively better among paediatric patients. We aim to review FMDs in children to better understand the different aspects of their frequency, clinical features, precipitating factors, diagnosis, treatment, and outcome.